Determinants of acceptance of patients with heart failure and their informal caregivers regarding an interactive decision-making system: a qualitative study. Issue 6 (16th June 2021) - Zippel-Schultz, Bettina; Palant, Alexander; Eurlings, Casper; F Ski, Chantal; Hill, Loreena; Thompson, David R; Fitzsimons, Donna; Dixon, Lana J; Brandts, Julia; Schuett, Katharina Andrea; de Maesschalck, Lieven; Barrett, Matthew; et al.
Abstract : Objective: Heart failure is a growing challenge to healthcare systems worldwide. Technological solutions have the potential to improve the health of patients and help to reduce costs. Acceptability is a prerequisite for the use and a successful implementation of new disruptive technologies. This qualitative study aimed to explore determinants that influence the acceptance of patients and their informal caregivers regarding a patient-oriented digital decision-making solution—a doctor-at-home system. Design: We applied a semistructured design using an interview guide that was based on a theoretical framework influenced by established acceptance theories. The interviews were analysed using a content analysis. Setting: A multicentred study in four European countries. Participants: We interviewed 49 patients and 33 of their informal caregivers. Most of the patients were male (76%) and aged between 60 and 69 years (43%). Informal caregivers were mostly female (85%). The majority of patients (55%) suffered from heart failure with mild symptoms. Results: Four main categories emerged from the data: needs and expectations, preferences regarding the care process, perceived risk and trust . Participants expressed clear wishes and expectations regarding a doctor-at-home, especially the need for reassurance and support in the management of heart failure. They were receptive to changes to the current healthcare processes. However, trust was identified as an important basis for acceptance and use. Finally, perceived risk for decision-making errors is a crucial topic in need of attention. Conclusion: Patients and informal caregivers see clear benefits of digitalisation in healthcare. They perceive that an interactive decision-making system for patients could empower and enable effective self-care. Our results provide important insights for development processes of patient-centred decision-making systems by identifying facilitators and barriers for acceptance. Further research is needed, especially regarding the influence and mitigation of patients and informal caregivers' perceived risks.